IMPLEMENTASI KEBIJAKAN PENANGANAN PENGAMEN JALANAN DI KOTA SERANG - Iip Mualip, Angga Rosidin (JURNAL PENELITIAN PENDIDIKAN SOSIAL HUMANIORA, 2022)
This study aims to: Knowing how the implementation of the Mayor of Serang Regulation Number 41 of 2017 concerning the Implementation of Regional Regulation Number 2 of 2010 concerning the Prevention, Eradication and Management of Community Diseases (Policy for Handling Street Singers in Serang City)". This study seeks to understand how the implementation of the policy of handling street buskers in the city of Serang in the regional regulation of Serang City number 2 of 2010 concerning the prevention of eradication and control of community diseases. Therefore, the approach used in this study is a qualitative approach. Research results from the Social Service and Civil Service Units to jointly prepare training support facilities for street buskers; Resources in handling street buskers, Serang City government involves social institutions and street children observers to support policy implementation; Communication between implementing agencies, as in the regional regulation that each agency takes its own role and cooperates and strengthens each othe